Extinguishing the flames of inflammation: retardant effect of chlorquinaldol on NLRP3-driven diseases - Zhilei Wang; Jingwen Liu; Yu Mou; Yuchen Li; Wenhao Liao; Menglin Yao; Ting Wang; Hongping Shen; Qin Sun; Jianyuan Tang (Molecular Medicine)
Abstract Background NLRP3 inflammasome immoderate activation results in the occurrence of various inflammatory diseases, but the clinic medications targeting NLRP3 inflammasome are still not available currently. The strategy of drug repurposing can reorient the direction of therapy, which is an indispensable method of drug research. In this study, an antimicrobial agent chlorquinaldol (CQ) was conducted to assess the effect on NLRP3 inflammasome and novel clinical value on NLRP3-driven diseases. Methods The effect of CQ on NLRP3 inflammasome activation and pyroptosis was studied in mouse and human macrophages. ASC oligomerization, intracellular potassium, reactive oxygen species production, and NLRP3-ASC interaction were used to evaluate the suppression mechanism of CQ on inflammasome activation. Finally, the ameliorative effects of CQ in the model of LPS-induced peritonitis, dextran sodium sulfate (DSS)-induced colitis, and monosodium urate (MSU)-induced gouty arthritis were evaluated in vivo. Results CQ is a highly powerful NLRP3 inhibitor that has feeble impact on the NLRC4 or AIM2 inflammasome activation in mouse and human macrophages. Further study indicated that CQ exhibits its suppression effect on NLRP3 inflammasome by blocking NLRP3-ASC interaction and hydroxyl on the benzene ring is vital for the assembly and activation of NLRP3 inflammasome. Furthermore, in vivo experiments demonstrated that administration of CQ has outstanding therapeutic action on LPS-induced peritonitis, DSS-induced colitis, and MSU-induced gouty inflammation in mice. Conclusions Collectively, the current study discoveries the antimicrobial agent CQ as a potentially specific NLRP3 inhibitor, and its use provides a feasible therapeutic approach for the treatment of NLRP3-driven diseases.